Application of Index Theory in the Study of Special Points of Differential Equations - Bazar, Khusanov; Fakhriddin, Fatkhullayev (European Journal of Life Safety and Stability (2660-9630), 2022)
This article studies the joint existence of singular points of a system of the form where and and are homogeneous polynomials of degree n with constant coefficients . For this purpose the index theory is applied and the characteristics of a singular point are calculated.